Cesarian section and long-term outcomes for cownose rays (Rhinoptera bonasus) - Buckner, Chris; George, Robert H.; Bulman, Frank; Durrett, Jared; Handsel, Tim; Wyffels, Jennifer T. (Frontiers in Veterinary Science, 2024)
Cownose rays (Rhinoptera bonasus) are schooling rays commonly displayed in large groups in public aquariums. They are long-lived, have an annual reproductive cycle, and readily breed in managed care with most pregnancies culminating with the unaided and successful birth of a single neonate. Occasionally, females are observed to have prolonged pregnancies or suffer dystocia during parturition and intervention via a cesarian section (C-section) is required to deliver the neonate. Monthly reproductive monitoring at Ripley’s Aquarium of the Smokies using ultrasound to stage pregnancies allows for the prediction of anticipated due dates and guides the decision to assist with delivery. Recognizing when to assist birth and best practices for performing C-section are important for the reproductive health, sustainability, and longevity of this species in managed care. This report describes a surgical technique for C-section in cownose rays and includes short-term complications and long-term outcomes for females.